Uji Keefektivan Ekstrak Beberapa Biji Tanaman untuk Menghambat Pertumbuhan Bakteri Bercak Daun (Xanthomonas campestris) pada Tanaman Tomat - DELVIANA PANJAITAN; I KETUT SUADA; MADE SRITAMIN (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Effectiveness Test of Some Plant Seeds Extract to Inhibit the Growth of Spotting Leaf Bacteria (Xanthomonas campestris) on Tomato Plant. The X. campestris bacterium is very harmful to tomato plant because the bacteria able to attack the plant seedling up to full grown stage. This bacterium not only attack the root, but also infect the leaves, fruits and stems. Utilization of botanical pesticides to inhibit the pathogen becomes one alternative option to be recommended. The control method has selective activity and safe for the ecosystem. The purpose of this study is to determine the ability of some plant seeds extract in inhibiting the growth of X. campestris the causal agent of leaf spot on tomato plants. Rose apple seed extract contains phyto-pesticide that can be used to inhibit the growth of leaf spot caused by X. campestris. The minimum inhibitory concentration of the extract was at a concentration of 0.312% with the diameter of inhibition zone of 8 mm. It was expected that rose apple seed extract may be used as an alternative subtance to inhibit the growth of bacterium X. campestris bacterium of tomato plants. Key words: plant seeds extract and Xanthomonas campestris